1977
DOI: 10.1007/bf00121976
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Priestley-Taylor evaporation model to assess the influence of soil moisture on the evaporation from a large weighing lysimeter and class a pan

Abstract: The influence of soil moisture on evaporation from a 6-m grass-covered lysimeter and from Class A pans was assessed for one summer using the a-parameter of the Priestfey-Taylor evaporation model appropriate for the individual surfaces computed on a daily basis. Net radiation over the pan was estimated from above-grass measurements using a correlation established between the hvo, using measurements made in the previous two summers. Changes in heat storage of the water were considered in the derivation of a for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
2
11
0
2
Order By: Relevance
“…The CY values for the clear-cut site are similar in rnagnitude to those reported by a number of other workers for similar short canopies under wet, dry, and all conditions (Wilson and Rouse 1972;Davies and Allen 1973;Mukammal and Neumann 1977). The forest results indicate that, over a wide range of conditions, the equilibrium model overestimates actual evapotranspiration rates when the canopy is dry.…”
Section: Precipitation and Soil Moisture Regimesupporting
confidence: 83%
“…The CY values for the clear-cut site are similar in rnagnitude to those reported by a number of other workers for similar short canopies under wet, dry, and all conditions (Wilson and Rouse 1972;Davies and Allen 1973;Mukammal and Neumann 1977). The forest results indicate that, over a wide range of conditions, the equilibrium model overestimates actual evapotranspiration rates when the canopy is dry.…”
Section: Precipitation and Soil Moisture Regimesupporting
confidence: 83%
“…This could be caused by a combination of heterogeneity in rainfall; local differences in responses from within the many upstream rivulets that still make up the upstream catchments; local storage areas not accounted for in my summary of land use; and differences in the absorption capabilities of vegetative cover over time. I hypothesize that the most likely cause of this finding is that at this grain size there remains considerable variation in plant cover and that differences in absorption rates are large as plants grow (Mukammal and Neuman 1977). At present we have no means of attributing individual vegetative cover types and thereby accounting for these potential differences.…”
Section: Significant Predictors Of Peak Dischargementioning
confidence: 84%
“…Mukammal and Neuman (1977), working north of Toronto, in proximity to my study area determined that actual evapotranspiration ranged from 1.0 to 6.5 mm/day. This effect has been demonstrated in several studies (Finch 1998 (2001) found that the greatest variability in the relationship between flows and forest cover is within the deciduous and mixed-deciduous forest types, common to this study area.…”
Section: Significant Predictors Of Peak Dischargementioning
confidence: 99%
“…The value of α was seen to vary slightly around 1.26 in most of the previous studies (e.g., Davies and Allen, 1973;Mukammal and Neumann, 1977;Stewart and Rouse, 1977;Thompson, 1975). The α = 1.26 is also used here.…”
Section: Aa Modelmentioning
confidence: 99%